2019
DOI: 10.1002/anie.201904445
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Time‐Tunable Emissions in Core–Shell Upconverting Nanoparticle Systems

Abstract: Color‐tunable luminescence has been extensively investigated in upconverting nanoparticles for diverse applications, each exploiting emissions in different spectral regions. Manipulation of the emission wavelength is accomplished by varying the composition of the luminescent material or the characteristics of the excitation source. Herein, we propose core–shell β‐NaGdF4: Tm3+, Yb3+/β‐NaGdF4: Tb3+ nanoparticles as intrinsic time‐tunable luminescent materials. The time dependency of the emission wavelength only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 64 publications
2
29
0
Order By: Relevance
“…3 These properties affect the overall optical characteristics of the materials, such as the absorption and emission bandwidth, the absorption crosssection, the probability of energy transfer and the population mechanisms of the different excited states. [4][5][6][7][8] Mahalingam et al rst described the synthesis of LiYF 4 :Yb 3+ ,Tm 3+ UCNPs and reported the upconverted emissions from the UV to the NIR upon 980 nm excitation. 9 Taking advantage of the high depth penetration, reduced photodamage and minimal autouorescence of the NIR excitation light, Tm 3+ -doped upconverting nanoparticles have found applications in drug delivery systems and in photodynamic therapy.…”
Section: Introductionmentioning
confidence: 99%
“…3 These properties affect the overall optical characteristics of the materials, such as the absorption and emission bandwidth, the absorption crosssection, the probability of energy transfer and the population mechanisms of the different excited states. [4][5][6][7][8] Mahalingam et al rst described the synthesis of LiYF 4 :Yb 3+ ,Tm 3+ UCNPs and reported the upconverted emissions from the UV to the NIR upon 980 nm excitation. 9 Taking advantage of the high depth penetration, reduced photodamage and minimal autouorescence of the NIR excitation light, Tm 3+ -doped upconverting nanoparticles have found applications in drug delivery systems and in photodynamic therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The intrinsic luminescence characteristics of UCNPs offers such a possibility, since the time interval between two intercorrelated emissions does not change with the velocity of the nanoparticle and can act as such a reference. [ 14 ] In this communication, we prove that the emissions from Tm 3+ and Tb 3+ in NaGdF 4 :49% Yb 3+ , 1% Tm 3+ /NaGdF 4 :20% Tb 3+ core–shell UCNPs respect the requirements for such a reference value. Consequently, velocity measurements were performed with these core–shell UCNPs in a toluene flow without the need for calibration or a sophisticated experimental setup.…”
Section: Figurementioning
confidence: 64%
“…The engineered core–shell UCNPs have a characteristic hexagonal prism shape (20 × 10 nm), forming colloidal suspensions in toluene. [ 14 ] The flow of toluene in the investigated velocity range between 1 and 1000 mm s ‐1 follows the so‐called laminar flow regime. The flow immediately around a nanoparticle with the same geometry of the proposed nanoprobes was preemptively simulated to verify that homogeneous flow [ 15,16 ] was not disrupted by the particles during the measurements and to evaluate the flow characteristics before performing the experiments (Appendix S1, Supporting Information).…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations